Pengaruh Endoxan-Asta (Cyclophosphamide) pada Pertumbuhan Embryo Ayam - Sri Sudarwati; Tien Wiati Suryono (Journal of Mathematical and Fundamental Sciences, 1975)
Ringkasan. Telah diteliti pengaruh Endoxan-Asta (cyclophosphamide) terhadap pertumbuhan embryo ayam dengan jalan menyuntikkannya ke dalam kantung yolk pada umur 4 dan 5 hari inkubasi. Didapatkan, bahwa dosis teratogenic adalah 0.04 mg per telur. Malformasi yang ditimbulkannya adalah: gelembung meliputi mata, kelopak mata yang tidak tumbuh dengan sempurna, mata yang tidak tumbuh samasekali, paruh dengan sisi lateral yang bercelah, paruh bawah atau paruh atas yang pendek, paruh menyilang, micromelia, syndactyli, ectrodactyli, ectopia viscerum, exencephali dan "cleft palate". Selain itu Endoxan-Asta berpengaruh menghambat pertumbuhan pada umumnya. Abstract. The influence of Endoxan-Asta (Cyclophosphamide) on the development of chick embryos has been investigated by injecting the substance into the yolk sac of 4 and 5 days incubated eggs. It was found that 0.04 mg Endoxan-Asta per egg is a teratogenic dose. Malformations obtained during the investigation were: bulb over the eye, eyelids not well developed, undeveloped eyes, cleft on the lateral sides of upper beak, short upper or lower beak, crossed beak, micromelia, syndactyly, ectrodactyly, ectopia viscerum, exencephaly and cleft palate. Besides that, Endoxan-Asta caused stunted growth.